DISCOVERY MODEL INTEGRATED WITH RELIGIOUS ASPECT IN BIOLOGY SUBJECT FOR IMPROVING SCIENTIFIC BEHAVIOUR - Mulyani, Aty; Rusdi, M.; Yelianti, Upik; Syahrial, Syahrial (Ibn Khaldun University, Bogor, 2020)
The aim of this study described about the integration between discovery models with religious aspect in Biology subject to develop student’s scientific behavior. Discovery is a systematic discovered learning model and each step of it gives an encouragement to do an investigation. Researcher combined each step of discovery syntax with religious aspect to give a simultaneously chance to the students, so they got scientific knowledge and religious aspect on Biology subject that they studied. There was no difference between science and religious aspect on learning method related to the concept mastery, 2) psychomotor; and 3) scientific aspect. Focus of this study was to develop scientific behavior such as curiosity, critical thinking, and honesty in Biology subject, because the teacher hadn’t integrated religious and scientific aspect during learning process, meanwhile the pattern of the integration through scientific process of syntax discovery. This study developed discovery learning models integrated with religious aspect through class action room research and it implements in Senior High School/Islamic Senior High School. This instructional procedure concept discovery model integrated with religious aspect using Lee and Jang’s procedure (2014). Need analysis, design, implement, and evaluate relate to discovery learning design integrated with religious aspect on Science (Biology) learning. The process by discussing, asking, answering, investigating, experimenting, interviewing, and the appropriate learning source based on science material to improve student’s scientific behavior in Senior High School relate to curiosity, critical thinking and honesty.